Creación y destrucción de empleos en el sector manufacturero del Perú: 2002-2007 - Tello, Mario D. (2011)
By way of a set of productive factors from a sample of manufacturing firms that created and destroyed jobs in Peru’s formal manufacturing sector for the period 2002-2007, this paper estimates the conditional labor demand equation under three interpretations. The results of these assessments suggest that job creation and destruction were statistically related to positive and negative changes of real output respectively. However, the rates of change of these job flows were lower than those of the real output value. On the other hand, job flows were positively associated with firms’ degrees of processing. Other minor factors associated with job flows were the size of firms and the capital-labor ratio.